Colorimetric Sensors with Enhanced Sensitivity and Angle‐independence - Hiu Ning Tiffany Chui; Shu Yang (Advanced Sensor Research)
Abstract Sensors that can be portable and easy to read out are highly attractive for point‐of‐care. However, such sensors often suffer from low sensitivity for real‐life applications. Manipulating light interactions with materials to enhance sensitivity and ease of recognition has emerged as a promising approach. This review first introduces several color‐changing mechanisms from photochromic dyes, photonic crystals, and surface plasmon resonance of gold nanoparticles, followed by a discussion of various strategies leveraging these techniques to enhance sensing capability. Specifically, it highlights approaches for detecting small and similar molecules, such as morphine, fentanyl, and volatile organic compounds. Strategies for angle‐independent colorimetric sensing and mechanochromic force recording are also explored. The review concludes with perspectives on future directions and advancements in colorimetric sensor technologies.